The Role of Forest Trees in Indigenous Farming Systems as a Catalyst for Forest Resources Management in the Rural Villages of Cross River State, Nigeria (Global Journal of Human-Social Science, 2013)
The concern of humanity is the need to tackle the increasing challenges of severe degradation of the forest ecosystem and its resources. The study examined the critical role of forest tree species in indigenous farming systems on the management of forest resources in the rainforest villages of Cross River State, Nigeria. The participatory Rural Appraisal (PRA) method, household questionnaire survey, field inventory and measurement were used to generate the required data. The data were analyzed using statistics such as simple percentage, mean, standard deviation, tables, graphs, charts and one-way analysis of variance (ANOVA). The study result indicated that the practice of tree felling during land preparation for farming is a minority attribute of the study population. 69.91 percent of the people allow trees on farmlands during land clearance, while 31.09% are found in tree-felling.
Keywords: forest management; farming systems; inventory; resources; tree retention; sustainability